Research on the Improvement of the Suction Pipe of a Pneumo-Mechanical Spinning Machine - Jamshid Yuldashev Qambaraliyevich; Umarov Akbarjon Axrorjon o‘g‘li (Zien Journals, 2022)
In this article, the possibilities of improving the quality indicators of products by improving the operating parameters of the dust-removing air duct of the rotor spinning machine have been studied. The results obtained were analyzed and studie.
Keywords: maturity; fiber; vacuum; thread